Frecuencia de Erysipelothrix sp en cerdos beneficiados en el camal del Distrito de Florencia de Mora – Trujillo 2016. - Silva Mujica, Mirelly Nayarit (2016)
The objective of this research was to determine the frequency of Erysipelothrix sp in pigs benefited in the slaughterhouse district of Florencia de Mora - Trujillo 2016 , to do a systematic random sampling 196 samples obtained from swabbing the tonsils of Sus scrofa domesticus , was performed ,collecting " pig " domesticus , which were placed in test tubes containing Sodium azide Glucose broth and taken to the lab to be incubated at 37ºC during 48 hours. Subsequently, the hemolytic capacity assessment, which was made in Trypticase Soy Agar with sodium azide and supplemented with blood .For the identification of bacterial species and genus gram staining, catalase and biochemical tests, was conducted in Triple Sugar Iron Agar t. It was determined that Erysipelothrix sp frequency was 32.65 % of which corresponds to 13.26 % E. rhusiopathiae and E. tonsillarum 19.39 %._x000D_ Key words: Swine erysipelas ,Erysipelothrix rhusiopatiae, Erisipelothrix tonsillarum.